Distribusi dan Kemampuan Adaptasi Spodoptera frugiperda (J. E Smith) (Lepidoptera: Noctuidae) Terhadap Tanaman Inang pada Beberapa Ketinggian Tempat di Bali - LISTYAWATI, PUTU SUSY; WIJAYA, I NYOMAN; WIDANINGSIH, DWI; SUPARTHA, I WAYAN (Agrotrop : Journal on Agriculture Science; Vol 12 No 1 (2022), 2022)
Distribution and Adaptability of Fall Army Worm, Spodoptera frugiperda (J.E Smith) (Lepidoptera: Noctuidae) Against Host Plants at Several Altitudes in Bali . The armyworm pest ( Spodoptera frugiperda J.E. Smith) was first discovered attacking maize plants in Sumatra in 2019.These pests move very quickly from a wide range of altitude and host plant, while in Bali only discovered this pest attack maize plants at an altitude <500 meters above sea level (masl). The purpose of this study was to determine the distribution map of S. frugiperda, to determine the population and host plants in the field and to determine the attack of S. frugiperda at several altitudes in Bali. This study used purposive survey method. Plant sampling was carried out in all regencies of Bali Province by means of diagonal sampling. The size of unit sample was2 x 2 m and the number of plants observed was 20 plants. The results showed that the pest S. frugiperda had spread in the highland up to (> 1000 masl) which attacked maize and sorghum in Bali. The distribution area of the pest are Tabanan, Badung, Gianyar, Klungkung, Karangasem, Bangli, Buleleng, Jembrana and Denpasar. The population of S. frugiperda was found until the highland (> 1000 masl) with a population of host plants is still low and spread at 5 altitude with type host plants found, sweet corn, glutinous corn, corn pipil , local corn and sorghum. he percentage of S. frugiperda attacks at 5 altitudes in Bali is 11.71% to 35.13%.